ANALYSIS OF THE EFFICIENCY OF USE OF THE EXPENDITURE BUDGET IN THE DIRECTORATE GENERAL OF PUBLIC HEALTH MINISTRY OF HEALTH REPUBLIC OF INDONESIA - Sanjaya , Rudy; Lativa, Lativa; Rahayu, Krida P (ADPEBI, 2022)
The aim of the research is to analyze the efficiency of budget realization and its impact on government performance at the Directorate General of Public Health, Ministry of Health, Republic of Indonesia. As a population and sample, namely the Work Unit (Satker) within the Directorate at the Directorate General of Public Health, Ministry of Health of the Republic of Indonesia during the 2016-2020 research period. Methods of data analysis using qualitative data analysis. The results of the observation can be concluded that if referring to the Directorate General of Treasury Regulation No. PER-5/PB/2022 concerning Technical Guidelines for Evaluation of Performance Indicators for Implementation of Ministries/Institutions Expenditure Budgets, the realization of personnel expenditure budgets, goods expenditures and capital expenditures in Work Units within the Directorate General of Public Health in 2016 was not efficient, in 2017 it was efficient, in 2018 it has been efficient, in 2019 it has been efficient and in 2020 it has been efficient. The aim of the research is to analyze the efficiency of budget realization and its impact on government performance at the Directorate General of Public Health, Ministry of Health, Republic of Indonesia. As a population and sample, namely the Work Unit (Satker) within the Directorate at the Directorate General of Public Health, Ministry of Health of the Republic of Indonesia during the 2016-2020 research period. Methods of data analysis using qualitative data analysis. The results of the observation can be concluded that if referring to the Directorate General of Treasury Regulation No. PER-5/PB/2022 concerning Technical Guidelines for Evaluation of Performance Indicators for Implementation of Ministries/Institutions Expenditure Budgets, the realization of personnel expenditure budgets, goods expenditures and capital expenditures in Work Units within the Directorate General of Public Health in 2016 was not efficient, in 2017 it was efficient, in 2018 it has been efficient, in 2019 it has been efficient and in 2020 it has been efficient.